2022
DOI: 10.3390/ijerph19148473
|View full text |Cite
|
Sign up to set email alerts
|

SarQoL Questionnaire in Community-Dwelling Older Adults under EWGSOP2 Sarcopenia Diagnosis Algorithm: A New Screening Method?

Abstract: This article is an observational and cross-sectional study that related the result obtained in the questionnaire for the evaluation of quality of life related to muscle mass (SarQoL) and the prevalence of sarcopenic pathology measured under the EWGSOP2 algorithm. Participants were 202 community-dwelling older adults living in Valencia, Spain. The prevalence of sarcopenia in men was 28.9%, while in women it was 26.2%. In the case of the SarQoL questionnaire, the mean score obtained for men was 75.5 and 72.6 for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
(122 reference statements)
1
6
1
6
Order By: Relevance
“…This difference may be due to the fact that the prevalence estimate was obtained from just two studies of those included in the meta-analysis [ 39 ]. Furthermore, there may be possible variations by race, age, or study setting, as similar figures are observed in similar populations [ 18 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This difference may be due to the fact that the prevalence estimate was obtained from just two studies of those included in the meta-analysis [ 39 ]. Furthermore, there may be possible variations by race, age, or study setting, as similar figures are observed in similar populations [ 18 ].…”
Section: Discussionmentioning
confidence: 93%
“…The application of the sarcopenia assessment algorithm, based on the EWGSOP2 criteria, and the sarcopenic obesity algorithm, based on the EASO/ESPEN criteria, is relatively time-consuming and resource-intensive, underscoring the need for more abbreviated screening instruments such as the Sarc-F or the Mini Sarcopenia Risk Assessment (MSRA). Health-related quality of life could also be used for screening, and since a specific QoL questionnaire (SarQol) became available, several cutoff points have been proposed, from ≤ 52.4 points [ 17 ] to ≤ 60 points [ 18 ]. These thresholds could be useful for screening older people with sarcopenia, providing an acceptable screening accuracy in relation to Sarc-F. That said, confirming the cutoffs with other population cohorts is still necessary [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The list of excluded studies and their respective reasons of exclusion is available on our Open Science Framework deposit (https://osf.io/rqhvy/). Therefore, a total of 43 observational studies were included in this systematic review, 42 cross‐sectional studies 5,27–67 and one prospective study 68 for which baseline values of HRQoL for the sarcopenic and non‐sarcopenic groups were used (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a study suggested a correlation between the SarQoL score and the risk level of suffering sarcopenia [51]. 60 points was the cut-off between high and moderate risk of sarcopenia.…”
Section: Discussionmentioning
confidence: 99%